Population-based incidence and 5-year survival for hospital-admitted traumatic brain and spinal cord injury, Western Australia, 2003-2008 - Moorin, Rachael; Miller, T.; Hendrie, Delia (Dr Dietrich Steinkopff Verlag, 2014)
This study aimed at analysing first-time hospitalisations for traumatic brain injury (TBI) and spinal cord injury (SCI) in Western Australia (WA), in terms of socio-demographic profile, cause of injury, relative risks and survival, using tabular and regression analyses of linked hospital discharge and mortality census files and comparing results with published standardised mortality rates (SMRs) for TBI. Participants were all 9,114 first hospital admissions for TBI or SCI from 7/2003 to 6/2008, linked to mortality census data through 12/2008, and the main outcome measures were number of cases by cause, SMRs in hospital and post-discharge by year through year 5. Road crashes accounted for 34 % of hospitalised TBI and 52 % of hospitalised SCI. 8,460 live TBI discharges experienced 580 deaths during 24,494 person-years of follow-up. The life-table expectation of deaths in the cohort was 164. Post-discharge SMRs were 7.66 in year 1, 3.86 in year 2 and averaged 2.31 in years 3 through 5. 317 live SCI discharges experienced 18 deaths during 929 years of follow-up. Post-discharge SMRs were 7.36 in year 1 and a fluctuating average of 2.13 in years 2 through 5. Use of data from model systems does not appear to yield biased SMRs. Similarly no systematic variation was observed between all-age studies and the more numerous studies that focused on those aged 14 to 16 and older. Based on two studies, SMRs for TBI, however, may be higher in year 2 post-discharge in Australia than elsewhere. That possibility and its cause warrant exploration. Expanding public TBI/SCI compensation in WA from road crash to all causes might triple TBI compensation and double SCI compensation.